2009
DOI: 10.2343/geochemj.1.0007
|View full text |Cite
|
Sign up to set email alerts
|

Grain size effect on Sr and Nd isotopic compositions in eolian dust: Implications for tracing dust provenance and Nd model age

Abstract: Strontium (Sr) and neodymium (Nd) isotopic compositions enable identification of dust sources and reconstruction of atmospheric dispersal pathways. The Sr and Nd isotopic compositions in eolian dust change systematically with grain size in ways not yet fully understood. This study demonstrates the grain size effect on the Sr and Nd isotopic compositions in loess and 2006 dust fall, based on analyses of seven separated grain size fractions. The analytical results indicate that Sr isotopic ratios strongly depend… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
58
0

Year Published

2011
2011
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 79 publications
(62 citation statements)
references
References 37 publications
4
58
0
Order By: Relevance
“…Grain size may influence Sr isotope ratios of detrital materials due to varying mineralogy, and hence isotopic compositions of fractions of different sizes. Fine-grained fractions tend to be enriched in radiogenic 87 Sr because of high Rb/Sr ratios in micas in general and biotite in particular (Dasch, 1969;Feng et al, 2009). In contrast, fractions of different sizes from the same source have similar ε Nd values (i.e., Nd isotope composition is almost independent of grain size), which allows for reconstruction of particle provenance in deep-sea sediments (Goldstein et al, 1984;Jiang et al, 2013;Tütken et al, 2002).…”
Section: Detrital Sediment Provenancesmentioning
confidence: 93%
“…Grain size may influence Sr isotope ratios of detrital materials due to varying mineralogy, and hence isotopic compositions of fractions of different sizes. Fine-grained fractions tend to be enriched in radiogenic 87 Sr because of high Rb/Sr ratios in micas in general and biotite in particular (Dasch, 1969;Feng et al, 2009). In contrast, fractions of different sizes from the same source have similar ε Nd values (i.e., Nd isotope composition is almost independent of grain size), which allows for reconstruction of particle provenance in deep-sea sediments (Goldstein et al, 1984;Jiang et al, 2013;Tütken et al, 2002).…”
Section: Detrital Sediment Provenancesmentioning
confidence: 93%
“…This is probably due to the presence of secondary carbonates. Several studies have shown that strontium isotope ratios in aeolian sediments are grain-size dependent and increase with decreasing grain size, since more radiogenic Sr is present in the ne fraction [42]. This coupling between grain size and Sr/ Sr ratio is usually not observed for Nd/ Nd.…”
Section: Ucc-normalized Spider Diagramsmentioning
confidence: 99%
“…This coupling between grain size and Sr/ Sr ratio is usually not observed for Nd/ Nd. The authors conclude that isotopic compositions should be measured on speci c grain size fractions of the samples instead of using bulk material [5,12,42]. However, there is some debate on this topic and other authors have argued that it is only the bulk fraction that contains the entire source area information of a sample [9,10,15].…”
Section: Ucc-normalized Spider Diagramsmentioning
confidence: 99%
“…Bulk Nd and Sr isotopic techniques are generally considered more reliable source tracers in fine-grained sediments Goldstein et al, 1984;Hemming et al, 1998;Goldstein and Jacobsen, 1988;McLennan et al, 1990;Clift et al, 2008;McLennan et al, 1990) but even these isotopic systems can vary with grain size within the fine-grained fraction (Feng et al, 2009). Sr isotopes can also be influenced by low-temperature alteration and variations in chemical vs. physical weathering (Clauer and Chaudhuri, 1995).…”
Section: Introductionmentioning
confidence: 99%